SUGARCANE ROOT SYSTEM OF RB855536 VARIETY PLANTED IN ONE BUD AND THREE BUDS SETTS - BUSO, Pedro Henrique de Medeiros; KOEHLER, Henrique Soares; DAROS, Edelclaiton; ZAMBON, José Luis Camargo; IDO, Oswaldo Teruyo; BESPALHOK-FILHO, João Carlos; WEBER, Heroldo; OLIVEIRA, Ricardo Augusto; ZENI NETO, Hugo (Scientia Agraria, 2009)
This work aimed to study the sugarcane root development in two different planting systems: using one bud setts and three buds setts. The experiment took place in Estação Experimental de Paranavaí, county of Paranavaí-PR, Agricultural Science Sector, Federal University of Paraná during the period of June 27th 2000 until July 10th 2001. The delineation was design as random blocks, with two ways of planting. Evaluation was performed 9 times during the 378 days cycle. The way and the depth of planting did not alter the length and diameter of the root system. In the two ways of planting it was verified that the variables specific surface and root system volume in the 00-20 cm depth were significantly higher. In the one bud setts system, it was observed a priority of root growth in length, a characteristic that can be important to drought conditions.